Enhancing Firm Financial Position by Reducing White Collar Crime through Financial Crime Control Remedies: a study of KP Hospitals (Pakistan Journal of Commerce and Social Sciences (ISSN 1997-8553), 2014)
This study focuses on a sympathetic activation of a structure which encounters three factors namely; financial crime control remedy (FCCR), white-collar crime (WCC) and firm financial position (FFP). Questionnaires were distributed on cross-sectional basis among the staff members of 6 different private hospitals of Peshawar and Kohat cities of KP Pakistan. Structure equation modeling (SEM) was used to test the impact of predictors on response variable. The findings provided evidence on the dynamics of FCCR on controlling WCC which further leads to enhancement of FFP. The recommendation and future area of the research was also given in the study.